Challenges in Implementing Differentiated Instruction with a Deep Learning Approach: Evidence from Vocational High Schools in Indonesia - Israyani Masyita; Muhammad Tahir; Nur Aeni (Faculty of Education and Teacher Training of UIN Palopo, 2026)
The study aimed to find out the teachers’ challenges in implementing differentiated instruction and deep learning approach in vocational EFL classrooms. This research used a qualitative method design where consist of 5 teachers selected through purposive sampling technique. Data collection involved the classroom observations and teacher’s interview while researcher recorded their answer to get more detailed information about the phenomenon being studied. The data was analyzed by using the reflexive Thematic Analysis (TA) criteria which consists of some steps, begin from familiarization with data, coding, generating initial themes, developing and reviewing themes until presenting a detailed teacher’s reflexive journals. The findings revealed that teachers still lack of experience in implementing differentiated instruction through deep learning approach in their classrooms. Not only that, some teachers also still confused on how to accommodate a diverse array of student needs, interests, and ability levels which were the most important thing in differentiated instruction implementation and also deep learning where both of those approaches can encourage students to explore content deeply, think critically, and apply their learning in meaningful contexts which is necessity for preparing learners for the challenges of the future. However, successful implementation requires sustained effort, investment in technology, and continuous professional development. Practically, this research will help educators, teachers, authorized bodies, students, and researchers to know the challenges that hinder successful implementation of differentiated instruction especially for English subject in vocational high school.